Daily life frequently erupted like a slap: Elena Ferrante's Neapolitan Novels as narrative intertexts of 1970s Italian feminist praxis. Issue 8 (3rd August 2022) - Heaney, Emma
ABSTRACT: This article historicises Elena Ferrante's Neapolitan Series novels in terms of 1970s feminism. The novels provide a phenomenological account of the development of the autonomist Italian left in the 1970s, but unlike most histories of this process, they centre the gendered contradictions within that political milieu. This narrative arc demands to be contextualised with the ideas of Italian feminists Carla Lonzi, Mariarosa dalla Costa, and the major Anglophone thinkers of Marxist Feminism. The Neapolitan Series investigates the feminist potential of relationships among women, even women who have no political consciousness in the common sense of the term, a potential that is illuminated by contrast with the oppressive effect of the most ardent and sophisticated male Marxists. What is crucial however, and this is at the heart of this article, is the fact that Ferrante stages this skewering of male proletarian rebels amid the finely wrought depictions of the capitalist immiseration of working-class women's lives and the inanity of bourgeois feminism. In short, this essay uses Ferrante (and her sensational popularity) as a way of thinking about the current revival of interest in 1970s feminism as an expression of the desire to reconcile the central tenets of Radical and Marxist Feminisms.